A FIELD STUDY OF TOPICAL AND METHODOLOGICAL UNIVERSITY CLASSIFICATION OF PHD THESES PREPARED IN TURKEY IN THE PERIOD OF 2000-2015 - Solak, Bilal; Erdoğan, Sedat (Ankara Serbest Muhasebeci Mali Müşavirler Odası, 2016)
This study includes the methodological and the topical classifications of accounting PhD theses accessed from YOK thesis screening pages in the period of 2000-2015. The study, in the corresponding period, also investigates Turkish university rankings of used accounting topics in Ph.D. theses. Results have been revealed in three periods; 2000-2005 is the first period, 2006-2010 is the second period, and 2011-2015 is the third period. Rankings are reported for the 2000-2015 period which cover whole years of this study. The content analysis, which is one of the archival research methods, is used as the main research methodology of this study.Results reveal that survey and case study methodologies are two most commonly used methodologies and financial accounting and auditing topics are two most popular accounting topics in accounting PhD education. In terms of the number and the accounting topical diversity of the PhD thesis, Marmara University seems to be in a place apart from other universities.

Bu çalışma Türkiye'de 2000-2015 yılları arasındaki dönemde YÖK tez tarama sayfasından ulaşılan muhasebe alanında yayınlanmış olan doktora tezlerinin konu ve metodolojik olarak sınıflandırmasını içermektedir. Üniversitelerde yayınlanmış olan muhasebe doktora tezlerinin muhasebe konu başlıkları açısından sıralamalarını içermektedir. Sonuçlar birinci dönem 2000-2005, ikinci dönem 2006-2010 ve üçüncü dönemde 2011-2015 olmak üzere üç dönem halinde ortaya koyulmuştur. Sıralamalar tüm yılları kapsayan 2000-2015 dönemine göre raporlanmıştır. Çalışmada kullanılan temel araştırma metodolojisi arşivsel araştırma metotlarından birisi olan içerik analizidir. Sonuçlar, muhasebe doktora eğitiminde en çok tercih edilen metodolojilerin anket ve örnek olay, en çok tercih edilen çalışma alanlarının ise finansal muhasebe ve denetim olduğunu göstermektedir. Çalışılan doktora tezi sayısı ve tezlerde kullanılan muhasebe alanların çeşitliliği bakımından ise Marmara Üniversitesi’nin diğer tüm üniversitelerden çok daha farklı bir yerde olduğu görülmektedir.
TÜRKİYE’DE 2000-2015 YILLARI ARASINDA HAZIRLANMIŞ OLAN DOKTORA TEZ METODOLOJİLERİNİN ÜNİVERSİTELERE GÖRE SINIFLANDIRILMASINA YÖNELİK BİR ALAN ARAŞTIRMASI